59 Contribution of Age in Effectiveness of Slow Deep Breathing Maneuver in Patients with Hypertension. (November 2017) - Wiharja, Wendy; Pranata, Raymond; Fatah, Abraham; Deka, Hadrian; Damay, Vito A.
Abstract : Objective: Slow Deep Breathing (SDB) may decrease Blood Pressure through manipulation in sympathetic and parasympathetic pathway. Its effectiveness for acute reducing of Blood Pressure depends on many contributing factors. Our study aims to know the contribution of age while measuring the effectiveness of SDB maneuver. Method: Cross sectional method was used in this clinical research. Subjects were collected through simple randomized sampling. Inclusion criteria were all patients with essential hypertension ranging 40–65 years old, on the other hand patients with secondary hypertension and those who took medicine regularly was excluded. There were 24 male patients and 24 female patients. We categorized patients using age (<50 years old, 50–60 years old, and >60 years old). Before starting the maneuver, the subjects were trained to perform the maneuver (6 times respiratory cycle within 1 minute). Subjects perform the maneuver for 5 minutes. BP was measured before and after maneuver. All data were processed using SPSS Ver.22. Result: Analytical study using paired T-Test compared Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (SBP) pre- and post- maneuver, result showed: on age <50 years old; lowering SBP (× 10.91mmHg) DBP (× 7.27mmHg) P-value 0.0000, age 50–60 years old; SBP (× 9.80mmHg) DBP (× 7.50mmHg) p-value 0.0000, age >60 years old; SBP (× 9.80mmHg) DBP (× 6.00mmHg) p-value 0.0000. Conclusion: This maneuver's effectiveness depends on the compliance of lung capacity and how well the subjects follow the instruction to do the maneuver. Since we assume that subjects who older might have low compliance, then we did this study. Occasionally from the result, we conclude that age has no effect in effectiveness of the maneuver, so this maneuver is useful for everyone with secondary hypertension.